P1469Micra pacemaker implant at septal site induces a smaller increase on qrs duration than traditional pacemaker: a single center experience. (18th June 2020) - Zucchelli, G; Parollo, M; Barletta, V; Di Cori, A; Della Tommasina, V; Mazzocchetti, L; Viani, S; Giannotti Santoro, M; De Lucia, R; Segreti, L; Cellamaro, T; Paperini, L; et al.
Abstract: BACKGROUND: Leadless pacemakers have been introduced into the clinical practice as a breakthrough technology that could tackle most of the major sources of complication of traditional pacemakers (PM). The excellent safety profile and optimal electrical performance of Micra have been already largely described, nevertheless the impact on QRS duration has not been investigated so far. We aimed to compare changes in QRS duration after septal Micra implant in comparison to patients who received transvenous right ventricular leads in the same position. METHODS: We enrolled all patients who underwent Micra implantation (group 1) at our Center from April 2017 to March 2019. A septal placement was attempted in all cases. Duration of spontaneous and paced QRS and their difference (delta QRS) were measured using a polygraph. To provide a comparison group, we analyzed the QRS duration in a matched group of patients (group 2) who received a traditional single chamber pacing system with a transvenously implanted lead at septal position in the same period. Confounding variables that were used to provide the control group were age, sex, left ventricle ejection fraction, and rhythm at implant. High pacing threshold was defined as ≥1.0 V at pulse duration of 0.24 ms. RESULTS: Twenty-eight consecutive patients (mean age 78 ± 3 years; 71.43% males) who underwent successful Micra implant were enrolled. A septal position was achieved in all cases with a single device delivery in 17/28 patients (60.7%). Mean pacing threshold at implant was 0.56 ± 0.34V/0.24 ms with only 3/28 patients (10.7%) presenting a high pacing threshold. No significant differences in demographic, clinical characteristics and ventricular pacing site were observed between groups. QRS duration was slightly longer in group 1 compared to group 2 before implant (median 123 ms (IQR 104-146.5 ms) vs median 116 ms (IQR 90-125 ms); p = 0.09). Nevertheless, there was a significantly lower delta QRS after implant in Micra compared to the traditional pacing group (15.82 ± 31.77 ms vs 35.82 ± 22.13 ms, p = 0.008). CONCLUSION: Right ventricular stimulation induces ventricular dyssynchrony, which is correlated with the amount of QRS enlargement after pacing. Micra implant, in a non-apical position, produces significantly smaller changes on the QRS duration in comparison with transvenous lead implanted at the same site, although larger studies are necessary to confirm these results.